Teachers’ competency towards teaching performance of thinking skills in Science classroom - Kamarudin, Nurzatulshima (Global Academic Excellence, 2018)
The purpose of this paper is to briefly discuss teachers’ competency in teaching higher order thinking skills, or HOTS in the (science) classroom. Thinking skills has an essential outcome in the educational process. Yet, we realize that the teaching of thinking skills in secondary education is lacking. Many students are not able to think out of the box. Educators have recognized improving the quality of students’ thinking as a key issue. This concerns mainly, the ability of Malaysian students to think critically, creatively, and effectively. Improving the thinking and reasoning abilities of all students’ calls for substantial changes in the mission of schools, the preparation of future teachers, and the methods of instruction. Teaching thinking skills to promote students’ intellect has been a major challenge for educators for a long time and there are continual demands to improve students’ learning and thinking skills. Thus, teachers need to possess a body of knowledge and be able to apply that knowledge to a variety of situations within their professional setting.